Investigations into properties of mineral wool slabs of increased stiffness manufactured of a large–size beam/Padidinto standumo mineralinės vatos plokščių, pagamintų iš suformuoto stambių gabaritų masyvo, savybės - Šakmanas, Aloyzas (Journal of Civil Engineering and Management, 1997)
The article presents the results of experimental investigations into non-uniformity of bulk density distribution, compressive strength, heat conductivity, and completion of binders polycondensation in slabs manufactured from a large-size mineral wool beam (its width B = 1000 mm and thickness H = 500 mm). The non-uniformity of bulk density was investigated as in a beam (for this purpose from different places of a beam there were cut samples with a thickness d = 120 mm), as in slabs (their length L = 1000 mm and width H = 500 mm). For such a purpose samples or slabs were cut after scheme (Fig 1) determining bulk density of each paralellepiped gi-j . The non-uniformity of bulk density was evaluated by values K H and K V , representing a relative departure from beam or slab bulk density gm. These values were calculated after formulae (1) and (2) where gi is the i-th vertical layer bulk thickness; gj is the j-th horizontal layer bulk thickness, n is number of vertical layers, m is number of horizontal layers. Variation of values K H and K V shows that relative departure from slab or beam bulk density does not exceed ± 20% (Fig 2). Comparing our experimental data with standard GOST 9573–82 requirements, one can see that compressive strength values of slabs s can exceed the standard one up to two times without increasing their bulk density (Fig 3). Better results are obtained when the content of binders is greater (within standard requirements). Also, it is possible to see that heat conductivity l because of structural changes of fibres distribution in a slab slightly increases (not more than 5%), when we are comparing this heat conductivity value with a maximally admitted standard one (Fig 4). Employment of this method allows the production of slabs, the optimal thickness of which has the ability to change from 6 to 500 mm. The binders polycondensation in such slabs is fully completed. Such slabs are suitable for insulating flat roofs, but their stiffness must be fastened by glueing them with stiff material. Article in Lithuanian. First Published Online: 26 Jul 2012